The Art of Comfort Mastering Housekeeping for the Ultimate Guest Experience - Kurniawan, Surya; Putri, Julian Andriani (International Journal of Economics, Business Management and Accounting (IJEBMA), 2024)
The Renaissance Okinawa Resort, a high-end resort situated in Japan, fully acknowledges the significance of housekeeping in crafting a memorable and exceptional stay for its patrons. Nevertheless, Renaissance Okinawa Resort is dedicated to upholding elevated levels of cleanliness and service by implementing inventive and effective housekeeping methods. A qualitative approach is a research method that focuses on understanding social phenomena from the perspectives of the people involved. The combination of detailed approach, extensive training, good communication, and teamwork enables them to provide an exceptional stay experience for every guest. Staying at Renaissance Okinawa Resort is described as one of the most comfortable experiences they have ever had, with high-quality rooms and highly personalized service creating a warm, friendly, and relaxed atmosphere. The housekeeping department at Renaissance Okinawa Resort demonstrates a proactive, flexible, and attentive approach in adapting their services to meet the diverse needs of guests. The combination of gathering guest preference information, adjusting amenities, using appropriate products, respecting cultural norms, good communication, creativity, and extensive training allows them to deliver a personalized and unforgettable stay experience for every guest